Impact of HR Policies and Practices on Employee Job Satisfaction: Evidence from Pakistan Telecommunication Ltd. (PTCL) Hyderabad, Pakistan - Amir Ali (SEISENSE (PRIVATE) LIMITED, 2019)
Aim - This research highlights the HR policies and practices in terms of compensation and performance evaluation and its impact on employee job satisfaction. This study will fill the gap in the literature by providing information on compensation and performance functions of human resource. Design - In this research descriptive design is taken in the collection of bias-free data. A sample of 42 respondents was taken into consideration from different management level of PTCL such as top, middle and lower level and the target population of this study was human resource department, management, and administrative staff. To collect the required information closed-ended questionnaire was used and were divided into three part; initially questionnaire identify the demographic factors of the respondents, then highlight the Likert scale options 1 being strongly disagreed and 5 strongly agree. Findings - In findings of this research we highly recommend the management to have fair and equitable compensation policies and establish performance evaluation system which can reduce to biases at all levels.